The Effect of Good Corporate Governance on the Financial Performance of Health Companies on the Indonesia Stock Exchange for the Years 2020-2023 - Ikhsannudin, Alif Wildan; Rochmatullah, Mahameru Rosy (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study aims to analyze the impact of Good Corporate Governance (GCG) on the financial performance of healthcare companies listed on the Indonesia Stock Exchange (IDX) during the period 2020-2023. The population of the study comprises 33 healthcare companies listed on the IDX, with a sample selected using purposive sampling based on criteria such as continuous listing and comprehensive financial reporting. Secondary data were obtained from annual reports published on the IDX's official website and individual company websites. The dependent variable in this study is the company's financial performance, measured by Return on Assets (ROA). The independent variables include Independent Commissioners, Audit Committee, Managerial Ownership, and Institutional Ownership. Data analysis was conducted using multiple linear regression with classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests, as well as hypothesis testing using t-tests, F-tests, and coefficient of determination (R²) tests, with SPSS 26. The results indicate that the Audit Committee and Managerial Ownership have a significant impact on the financial performance of healthcare companies. Conversely, Independent Commissioners and Institutional Ownership do not show a significant effect on the financial performance of healthcare companies during the study period.